2017
DOI: 10.1111/jfb.13247
|View full text |Cite
|
Sign up to set email alerts
|

First confirmed record ofMolasp. A in the western Mediterranean Sea: morphological, molecular and parasitological findings

Abstract: Recent molecular and morphological studies suggest the existence of at least three species of Mola (Mola spp. A, B and C). Currently, only Mola mola and Mola ramsayi are formally accepted and species A, B or C have not been assigned to these thus far. In this study, a large ocean sunfish in the western Mediterranean Sea was analysed molecularly and morphologically, identified as Mola sp. A and a detailed account of the specimen's parasite load is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…The third clade, Mola sp. B of Yoshita et al (2009), has been equated to M. mola (Yoshita et al 2009;Matsuura 2014;Sawai et al 2018), with residual uncertainties in the nomenclature, as this species appears to include two basin-wide groups (Atlantic vs Pacific), as revealed by phylogenetic analysis (Bass et al 2005;Ahuir-Baraja et al 2017;Sawai et al 2017). Here, the nomenclature follows Sawai et al (2018) by treating Mola sp.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…The third clade, Mola sp. B of Yoshita et al (2009), has been equated to M. mola (Yoshita et al 2009;Matsuura 2014;Sawai et al 2018), with residual uncertainties in the nomenclature, as this species appears to include two basin-wide groups (Atlantic vs Pacific), as revealed by phylogenetic analysis (Bass et al 2005;Ahuir-Baraja et al 2017;Sawai et al 2017). Here, the nomenclature follows Sawai et al (2018) by treating Mola sp.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, a legacy of taxonomic confusion (Nyegaard et al 2017;Sawai et al 2018) has obscured a more complex zoogeographical pattern within the Mola species. The traditional view of M. alexandrini being restricted to the South Pacific, with sympatric occurrence with M. mola in Australian waters (Fraser-Brunner 1951), has been challenged in recent years, as molecular, morphological and ecological studies have confirmed that M. alexandrini is found over a wide range in both hemispheres (Yoshita et al 2009;Thys et al 2013Thys et al , 2016Ahuir-Baraja et al 2017;Sawai et al 2018). Prior to its recent description, Mola tecta was mistaken for M. mola or M. ramsayi (now M. alexandrini) and while M. tecta appears to have a circumpolar distribution in temperate waters of the southern hemisphere (Nyegaard et al 2017), little is known of this recently described species.…”
Section: Distribution and Interactions With Fisheriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Os peixes da espécie Mola mola pertence a ordem Tetraodontiforme e a família Molidae (Ahuir-Baraja et al, 2017), conhecido popularmente como peixe Lua, peixe Sol ou molas. São encontrados nos oceanos Atlântico e Pacífico (Pope et al, 2010).…”
Section: Introductionunclassified